Konsep Marketing Berbasis Maqoshid Al-syari'i Imam Al-Ghazali - Ivan Rahmat Santoso (Jurnal Ilmiah Ekonomi Islam, 2019)
The thinking of the Imam Al-Ghazali socioeconomic Ra stem from a concept he called "Islamic social welfare functions". A theme that became the base of his entire starting is the concept of social welfare affairs or utilities (common good) contained in the maqasid Sharia. This study aims to formulate a concept of marketing based on the values mashlahat maqasid Sharia. The method of this research is kualitatid desktiptif with an approach to the study of librarianship.The research found that in designing the marketing pattern of marketers should pay attention to the concept of maslahah maqasid Sharia as a goal of as a guide in marketing strategies. Five things that go in Islamic trends i.e., religion, soul, intellect, lineage, and treasures are factors which becomes basic guidelines the lack of intervention. This design pattern, as a consequence of childbirth a maslahah therein.